ANALISIS PERBANDINGAN JUMLAH ALAT BERAT DENGAN PENERIMAAN PEMUNGUTAN PAJAK DARI TAHUN KE TAHUN DAN KONTRIBUSINYA DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH SULAWESI UTARA - Karels, Hana Glorya; Karamoy, Herman; Kalalo, Meily Y. B. (Universitas Sam Ratulangi, 2020)
Local governments always need local revenue sources that can support regional expenditure financing from various alternative revenue sources that may be collected by the region. Tax as the biggest source of state revenue has a tendency to increase from year to year. One of them is the motor vehicle tax, especially the heavy vehicle motor vehicle tax. The purpose of this study is to analyze the magnitude of the comparison of the number of heavy equipment from year to year with existing tax revenue, analyze its contribution in increasing local revenue and the obstacles faced in heavy equipment tax collection in North Sulawesi using descriptive qualitative research methods. Research results show that the number of heavy equipment that exists with the amount that pays heavy equipment tax has an unbalanced comparison from year to year. With an average number of revenues or tax realization of heavy equipment in the last 3 (three) years amounting to Rp. 198,250,854. The average heavy equipment tax contribution from 2016 to 2018 is only 0.18%, which shows very poor criteria. The existence of a lawsuit from the association of owners and users of heavy equipment that is still in the process of being one of the obstacles of collecting heavy equipment tax itself.